Pengembangan Booklet Kelainan Sistem Peredaran Darah Disertai Pengayaan Uji Aktivitas Antidislipidemia Ekstrak Daun Salam - Nur Dwi Handarsiputri; Titin Titin; Wolly Candramila (BIOEDUSCIENCE, 2022)
Background: Media booklets are media used in the learning process that have advantages in supportive conditions. The booklet contains a summary of the material that is equipped with pictures and colors so that it is interesting. This study aims to develop a booklet with enriched information about the antidyslipidemic activity test of bay leaf extract (Syzygium polianthum (Wight) Walp.) as a learning medium in the Sub Material of Circulatory System Abnormalities for second grade of highschool. Methods: This development research uses the type of research and development (R&D). The development stages include potentials and problems, data collection, product design, design validation, design revision, and product. The media booklet was validated by 5 validators in terms of format, content, and language, all of which covered 9 criteria. Results: Validation obtained Content Validity Ratio (CVR) and Content Validity Index (CVI) values "‹"‹of 1 which meet the minimum criteria for content validity. Conclusion: Thus, the booklet enriched with the results of the antidyslipidemic activity test of bay leaf extract (Syzygium polianthum (Wight) Walp.) was declared content valid as a learning medium in the Circulatory System Abnormalities Submaterial.